"Marxism in Contemporary Western Archaeology", Bruce G. Trigger in Archaeological Method and Theory, Volume 5, edited by Michael B . Schiffer. Tucson, Unversity of Arizona Press 1993 - James A. Delle (Bulletin of the History of Archaeology, 1993)
Professor Trigger's contribution to Schiffer's volune is a well-reasoned and significant consideration of the influence of Marxist thought on the work of number of contemporary archaeologists. He is more critical of recent developments within Marxist archaeology than is McGuire; the article stands as a challenge to those who utilize Marxist ideas to reconsider the direction they have lately taken. In this article Trigger demonstrates his thorough knowledge of both Marxist theory and the social history of archaeology (here I am following Trigger's convention by capitalizing "Marxist"). Although his consideration of the contributions of Marxists to Western archaeology is generally sympathetic. he is unafraid to criticize where he feels it is appropriate. Like McGuire, Trigger offers critical insight on the relationship between Marxist philosophy and archaeology; unlike McGuire, Trigger explicitly limits his discussion to Western Europe and North America.